The Effectiveness of Using Technology-Based Learning Media in Relation with Learning Achievement in English - Riandi, Riandi (Journal of English Education Studies, 2019)
Learning media is a tool to convey messages or information aimed at instructional or contain learning purposes that can be manipulated, seen, heard, and read. Learning achievement is the result achieved after conducting learning activities. Both learning are done formally and non-formally which includes three aspects of student change cognitive, affective and psychomotor. The use of technology contributes greatly to the improvement of student achievement in English subjects, therefore students who use technology-based learning media in the teaching and learning process in the classroom will get good learning achievements. This research was conducted at SMK Nurul Muhtadin Kibin Serang, with a sample size of 32 students, from a population of 160 students, the researcher took 20% of the sample students from the total population of research. The method used in this research is quantitative descriptive method with research instruments: tests, questionnaires and literature studies. The conclusion obtained from this study is the effectiveness of the use of technology-based learning media in Nurul Muhtadin Vocational High School obtained mean value = 54 Median = 53.68 and Mode = 53.04 and SD = 5.16 While English Learning Achievement obtained mean = 79.53 Median = 77.5 Mode = 70 and Sd = 13.01 whereas from the results of the normality test L = 0.886 is thus Lo (0.2047)> of L (0.886). So that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that the sample is normally distributed. While the effect of the effectiveness of the use of technology-based learning media in SMK Nurul Muhtadin Kibin Serang, quantitatively it has a relationship that is sufficient or moderate, this is evidenced by the correlation coefficient ("r") of 0.60, the value is at intertval 0.60-0.80. The contribution of variable X to variable Y by using coefficient of determination (Cd) is = 36% while the remaining 64% is influenced by other factors both internal and external